OPPORTUNITIES FOR IMPROVING THE COMPETITIVENESS OF RAIL FREIGHT TRANSPORTATION ALONG THE TRANSPORT CORRIDORS OF THE RUSSIAN FEDERATION - P. S. Kuzmin (Стратегические решения и риск-менеджмент, 2020)
The greatest prospects associated with transnational rail freight are determined by the use of containers. In Russian publications, the development of containerized cargo transportation is mainly considered by analyzing the general laws of functioning of international transport corridors. At the same time, aspects affecting infrastructure diagnostics and analysis of the throughput capacity of sections of the railway network are not considered.The purpose of the study was to identify the characteristics of freight flows in the direction of the EU—EAEU—PRC, to identify infrastructure barriers that slow down the acceleration and increase in the volume of container railway freight transportation, as well as to develop a set of measures aimed at improving the competitiveness of container railway freight transportation along the transport corridors of the Russian Federation.In the course of the study, infrastructural diagnostics was carried out, which revealed a number of barriers that did not allow realizing the growth potential of transit container cargo transportation.To remove infrastructure barriers, it is necessary to implement a number of measures, the key of which are measures to increase the capacity of infrastructure at border crossings, increase the speed of trains along the railway networks of JSCo RZD, develop terminal and logistics centers that provide a wide range of services for consignors and consignees.The development of container rail freight is a strategically important area for the Russian Federation. The well-coordinated work of Russian Railways with private investors and the state in the framework of expanding and modernizing the terminal infrastructure, as well as increasing intermodal interactions, is able to overcome the existing infrastructure barriers and ensure the growth of container transit in the required volumes.